Hubungan antara Fear of Missing Out (FoMO) dengan Subjective Well-Being pada Penggemar NCT Dream - Yoanita Maria Putri Sekar Gading; Agoes Dariyo (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
The presence of NCT Dream in Indonesia for their concert titled "The Dream Show" has become one of the K-Pop phenomena frequently discussed on social media. Fan engagement in their idol's concerts is linked to subjective well-being. Unfortunately, not all fans can attend The Dream Show concerts in person, so they tend to access social media intensively due to the feeling of FMO they experience. This research was conducted to determine the relationship between Fear of Missing Out (FoMO) and Subjective Well-Being in NCT Dream fans. This study used a purposive sampling technique and involved 169 NCT Dream fans residing in Jabodetabek, aged 18-25 years, and active on social media. The measurement tools used in this study were the Fear of Missing Out Scale (9 items, α = 0.877), the Satisfaction with Life Scale-Indonesia (5 items, α = 0.744), and the Positive and Negative Affects Schedule (9 items, α = 0.798 for the positive dimension and 9 items, α = 0.854 for the negative dimension). The results of the correlation analysis showed no relationship between Fear of Missing Out (FoMO) and Subjective Well-Being (r = -0,014, p = 0,430, p > 0,05).